Soil aggregation and carbon sequestration following a single tillage event in no-till soils in a semi-arid environment - Asmus, Chad Donald (Kansas State University, 2009)
The sequestration of atmospheric CO[subscript]2 into soil through no-till management is an economic and viable method for reducing greenhouse gases, but maintaining no-till practices are necessary to sequester C in the long-term. Our study focused on the effects of a single tillage operation on soil organic C and N and aggregation in no-till soils when no-till practices are immediately resumed after tillage. Three locations in western Kansas were selected that had been in continuous dryland no-till for at least 5 years – Wallace, Tribune, and Spearville. Tillage treatments were administered in 2004 and consisted of no-till (NT), disk plow (DP), sweep plow (SwP), and chisel plow (CP). Treatments were arranged in a randomized complete block design with four replications. Soil samples were taken at 0-5, 5-15, and 15-30 cm depths. Composite samples were taken from each block prior to tillage and tested for whole soil organic C and N. Further soil samples were collected in spring 2005 at approximately nine months after tillage (MAT) and again in fall 2005 at approximately 12 MAT and tested for whole soil organic C and N and aggregate size distribution. Bulk density was measured for each plot and depth prior to sampling at 12 MAT. Twelve MAT samples were also tested for aggregate-associated C and N. The DP tillage had a greater C concentration than NT and CP when averaged over depth and time, but C mass did not vary between tillage systems. Changes in whole soil C and N over time varied by location, but the differences were similar between tillage treatments. Tillage treatments DP and SwP also had a greater mass of macroaggregate (250-1000 [Mu]m) associated C relative to CP (but not to NT) for Wallace in the surface 0-5 cm at 12 MAT. No other differences between tillages in aggregate-associated C were observed. A single tillage event did not have a significant impact on aggregate size distribution. The greatest amount of aggregate-associated C and N existed in the large microaggregate (53-250 µm) fraction. Changes in aggregate distribution or aggregate-associated C or N did not directly correlate to changes in whole soil C and N. We therefore conclude that a single tillage operation using these implements will not result in a measurable loss in sequestered C over time for dryland soils in a semi-arid climate such as western Kansas.
Keywords: Carbon sequestration; No-till; Aggregates; Soil organic carbon; Tillage; Agriculture, Agronomy (0285); Agriculture, Soil Science (0481)